DEVELOPMENT AND ASSESSMENT OF A HERBAL SERUM FOR HAIR STRAIGHTENING (International Journal of Food and Nutritional Sciences, 2023)
Hair serums, particularly herbal hair straightening serums, are cosmetic products enriched with high concentrations of active ingredients aimed at deeply nourishing the skin layers without leaving a greasy residue. These serums often incorporate natural components such as plant extracts and oils. Depending on their formulation, herbal hair serums offer various benefits including scalp nourishment, promotion of hair growth, reduction of frizz, enhancement of shine, and protection against environmental damage. Herbal ingredients are known for their soothing properties and ability to maintain moisture balance. For instance, flaxseeds contain omega-3 fatty acids that provide essential proteins and nutrients to hair follicles, improve scalp circulation, and reduce inflammation that contributes to hair loss.